2021
DOI: 10.1016/j.bjid.2020.11.004
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 among nursing home residents: results of an urgent pre-hospital intervention by a multidisciplinary task force

Abstract: The current coronavirus disease-2019 (COVID-19) pandemic caused 10,541 deaths among nursing home residents in France, by July 17th, 2020. This study reported the results of an urgent pre-hospital intervention in eight French nursing homes. A retrospective study was conducted from March 26th to May 7th, 2020, before and after the intervention of a task force which took action from April 9th to April 11th, 2020. The task force included nurses and specialists of the county general hospital. The interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Besides vaccination, a more comprehensive organization for NH management is needed [ 33 , 34 ] in order to promote improved handling of COVID-19 and possibly of other epidemics in these facilities. Special attention should be paid also to enhance the engagement of physicians and nurse practitioners [ 35 ], with the aim to improve care for NH residents [ 36 , 37 ], also with prehospital interventions [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides vaccination, a more comprehensive organization for NH management is needed [ 33 , 34 ] in order to promote improved handling of COVID-19 and possibly of other epidemics in these facilities. Special attention should be paid also to enhance the engagement of physicians and nurse practitioners [ 35 ], with the aim to improve care for NH residents [ 36 , 37 ], also with prehospital interventions [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…They had been published in journals across a wide range of health science disciplines. The studies included different types of LTCF populations: older people who reside in nursing homes (Dichter, Sander, Seismann-Petersen, & Köpke, 2020;Dolveck et al, 2021;Gilbert, 2020;Mo & Shi, 2020;Wammes et al, 2020), nursing facilities (Maggie Collison et al, 2020;Song et al, 2020), as well as geriatric acute care units, long-term care, and nursing homes (E. E. Office, M. S. Rodenstein, T. S. Merchant, T. R. Pendergrast, & L. A. Lindquist, 2020; Sacco, Lléonart, Simon, Noublanche, & Annweiler, 2020). Several study designs were included in the review, as demonstrated in Supplementary Table 1.…”
Section: Study Participantsmentioning
confidence: 99%
“…All included articles were published in 2020 or 2021. In terms of geographical distribution, there are five studies from the USA (Abbasi, 2020;Maggie Collison et al, 2020;Lipsitz et al, 2020;Mo & Shi, 2020; E. E. Office et al, 2020), two from France (Dolveck et al, 2021;Sacco et al, 2020), two from Germany (Dichter et al, 2020;Follmann et al, 2021), one from Canada (Siu, Kristof, Elston, Hafid, & Mather, 2020), one from South Korea (Song et al, 2020), one from Australia (Gilbert, 2020), one from the Netherlands (Wammes et al, 2020), one from Brazil (Moraes et al, 2020), and two scoping reviews that include articles from varied countries around the world (Bethell et al, 2021;Mobasseri, Azami-Aghdash, Khanijahani, & Khodayari-Zarnaq, 2020).…”
Section: Bibliometric Categoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Altersgrenze wurde auf 80 Jahre festgelegt, da das Durchschnittsalter der Pflegebedürftigen in den berücksichtigten Jahren bei ca. 80 Jahren liegt [14] und Pflegebedürftige besonders von COVID-19 betroffen waren [15]. Alle Auswertungen wurden mit dem Programm Origin © 8.5 (Fa.…”
unclassified